Comparative effects of addition of superoxide dismutase and reduced glutathione on cryopreservation of Sahiwal bull semen - Murtaza, A.; Ahmad, M.; Zubair, M.; Umar, S.; Mushtaq, A.; Gul, A.H.S.T.; Khan, A. U. (Journal of the Hellenic Veterinary Medical Society, 2019)
The present study aimed to investigate effects of superoxide dismutase (SOD) and reduced glutathione (GSH) on the quality of frozen-thawed semen of Sahiwal bulls. Semen was collected twice a week for 8 weeks by artificial vagina from six Sahiwal bulls, kept at the Semen Production Unit Qadirabad, Sahiwal-Pakistan. After gross and microscopic evaluation, qualifying semen ejaculates were divided into 10 equal aliquots and diluted in extenders enriched with no antioxidants (control); or supplemented with either SOD (50, 100 and 200 IU/mL), or GSH (0.5, 1 and 2 mM) or their combinations (50 IU/mL SOD and 0.5 mM GSH, 100 IU/mL SOD and 1 mM GSH and 200 IU/mL SOD and 2 mM GSH). Samples were then frozen and stored in liquid nitrogen at -196°C for 24 h. The following parameters were evaluated for semen quality: post-thawed sperm motility, viability, acrosome and membrane integrity. According to the results, sperm motility, viability, acrosome and membrane integrity were significantly (P<0.05) higher in samples treated either with 100 IU/mL of SOD; 1 mM and 2 mM of GSH or 50 IU/mL of SOD plus 0.5 mM of GSH. In conclusion, semen quality might be improved by supplementing semen extenders with 100 IU/mL of SOD; 0.5 and 1 mM of GSH and combination of 50 IU/mL and 0.5 mM of SOD and GSH, respectively.